Integrating Islamic Religious Education Values into Entrepreneurship: A Contemporary Cultural Perspective - Hosaini (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2025)
This study explores the integration of Islamic Religious Education (PAI) values into contemporary culture-based entrepreneurship education. Amid global challenges and digital era dynamics, the presence of Muslim entrepreneurs who are ethical, spiritual, innovative, and adaptive is crucial. Employing a literature study method with a qualitative approach, the research analyzes sources related to Islamic values in education and entrepreneurship. The results show that core PAI values of honesty, trustworthiness, hard work, responsibility, and creativity can be integrated into entrepreneurship education through a holistic and contextual model. This model rests on four pillars: Islamic character formation, internalization of Sharia principles in business, development of value-based entrepreneurial skills, and real-world application in the community. The integration strengthens the Islamic identity of entrepreneurs while bridging religion and professional competence. This approach contributes to developing a contextual, relevant curriculum that embeds Islamic values in entrepreneurship education, offering a framework for producing ethically grounded Muslim entrepreneurs fit for modern challenges.